2021
DOI: 10.3389/fcell.2021.665673
|View full text |Cite
|
Sign up to set email alerts
|

A Covalent Calmodulin Inhibitor as a Tool to Study Cellular Mechanisms of K-Ras-Driven Stemness

Abstract: Recently, the highly mutated oncoprotein K-Ras4B (hereafter K-Ras) was shown to drive cancer cell stemness in conjunction with calmodulin (CaM). We previously showed that the covalent CaM inhibitor ophiobolin A (OphA) can potently inhibit K-Ras stemness activity. However, OphA, a fungus-derived natural product, exhibits an unspecific, broad toxicity across all phyla. Here we identified a less toxic, functional analog of OphA that can efficiently inactivate CaM by covalent inhibition. We analyzed a small series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 65 publications
7
52
0
Order By: Relevance
“…CaM can act as a trafficking chaperone of K-Ras by shielding the hydrophobic farnesyl tail from the aqueous environment of the cytoplasm, thus effectively increasing the diffusibility of K-Ras (22,40). In order to detect an effect of the CaM inhibitors on the K-Ras/ CaM interaction in cells, we established a BRET assay (22), where we genetically fused Rluc8 to the N-terminus of K-RasG12V and GFP2 to the N-terminus of CaM.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…CaM can act as a trafficking chaperone of K-Ras by shielding the hydrophobic farnesyl tail from the aqueous environment of the cytoplasm, thus effectively increasing the diffusibility of K-Ras (22,40). In order to detect an effect of the CaM inhibitors on the K-Ras/ CaM interaction in cells, we established a BRET assay (22), where we genetically fused Rluc8 to the N-terminus of K-RasG12V and GFP2 to the N-terminus of CaM.…”
Section: Resultsmentioning
confidence: 99%
“…Both the covalently reacting CaM inhibitor OphA and the non-covalent, highly potent calmidazolium reduced the BRET signal when tested across a wider concentration range, in agreement with their CaM inhibiting activity ( Figure 2B ). In order to robustly distinguish the magnitude of these effects, we analyzed the dose response data using a normalized area under the curve measure, the DSS 3 BRET -score (22,41). These data revealed that addition of the electrophile in Flu-M significantly increased the intracellular activity against CaM/ K-RasG12V as compared to its non-covalent counterpart Flu by more than a factor of two ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations